Managing Readers' Impressions of Research Article Abstracts Through Metadiscourse - Gustilo, Leah; Comillo, Maria Isabel; Valle, Aileen; Comillo, Rosendo III (Indonesian Journal of Applied Linguistics, 2021)
A plethora of research on academic discourse analysis has supplied empirical findings that readers’ impressions of texts can be managed through the utilization of metadiscoursal resources linked to the social intentions and practices of academic communities. However, the writers’ efforts in meeting the readers’ expectations through metadiscourse in the specific rhetorical moves of abstracts across disciplines have not been much researched. The study examines the rhetorical moves of research article abstracts (RAAs) and the distribution of metadiscourse markers (MDMs) across the identified moves using a corpus of 300 abstracts in four disciplines. The analysis shows that product, purpose, and method moves were given more prominence by most of the writers across disciplines. Transition markers were the most utilized interactive markers, while hedges and engagement markers were the most prominently used interactional markers. This study provides implications for research article abstract writers to manage readers’ impressions of texts and comply with the expectations of the discourse community in their respective fields.